MISKONSEPSI DAN SIKAP SISWA PADA PEMBELAJARAN LEMAK MELALUI PRAKTIKUM PEMBUATAN SABUN TRANSPARAN - Kadarohman, Asep; Nahadi, Nahadi; M., Mira Ratna Asri (Jurnal Pengajaran MIPA, 2010)
The students’ misconceptions and attitudes in teaching learning fat through transparent soap-making lab has been investigated. The study was conducted on 36 science students on the 3th grade at one of the state senior high school in Bandung. The research used descriptive method, with diagnostic tests, questionnaires attitude scale "Likert", observation, and interviews as the instruments. It was found that, 50% of students had misconceptions on physical properties of fats and oils concepts. The students had a good perception on teaching learning process as well as the relationship of fat with daily life.